Pendampingan dan Penguatan Kemampuan Kognitif Siswa Berkebutuhan Khusus di SLBN Kebayakan Aceh Tengah: Cognitive Intervention and Support Services for Students with Special Educational Needs at SLBN Kebayakan Aceh Tengah - Saputra, Edy; Harahap, Ahmad Yunus Mokoginta (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This service activity entitled "Cognitive Intervention and Support Services for Students with Special Educational Needs at SLBN Kebayakan Aceh Tengah" aims to provide support and improve cognitive abilities for students with special needs. The goal is more specifically focused on assisting and strengthening the cognitive abilities of students with special needs at the Kebayakan State Special School in Central Aceh by finding learning solutions that are effective for students with special needs. Systematic mentoring methods, focus on developing students' thinking, concentration, and problem-solving skills and increasing teachers' pedagogical abilities in implementing learning. The implementation of this program is carried out using a service learning approach which involves various interactive activities designed to meet students' individual needs, as well as increase their self-confidence and motivation in learning. The results of this activity show an increase in student's cognitive abilities, as well as increased involvement and active participation in the teaching and learning process. With this program, it is hoped that it can create a more inclusive and supportive learning environment for students with special needs so that they can optimize their potential. It is hoped that the results of this service will become the basis for developing similar programs in the future.